Self-supporting graphene oxide films preparation and characterization methods. (February 2019) - Torrisi, L.; Cutroneo, M.; Havranek, V.; Silipigni, L.; Fazio, B.; Fazio, M.; Di Marco, G.; Stassi, A.; Torrisi, A.
Abstract: Graphene oxide (GO) is prepared as a self-supporting thin film by a liquid solution of GO. The so-obtained GO films have been characterized in terms of thickness and density. The GO film composition and trace elements have been measured with Rutherford backscattering spectrometry (RBS) and Elastic recoil detection analysis (ERDA), using MeV helium ion beams. The presence of crystalline and amorphous phases has been also investigated with X-ray diffraction (XRD) and the morphology by scanning electron microscopy (SEM). Information about the GO film structure, oxidation degree and thickness has been deduced by means of Fourier transform infrared spectroscopy (FT-IR), Raman and optical spectroscopy (ultraviolet-visible-near infrared spectroscopy, UV-Vis-nIR). In particular, the GO film thickness varies from sub-micrometric values up to micrometric ones. Furthermore, the GO film heating in air up to 60 °C produces oxidation effects as deduced from the interpretation of our data. Highlights: Graphene oxide and reduced graphene oxide have special properties and can be used in different fields with micro- and sub-micrometric thickness. Graphene oxide is prepared by chemical and physical method as a self-supporting film with different thickness. The preparation in air at room temperature produces graphene oxide with less oxygen and hydrogen content compared to that prepared at 60°C. The ion or laser irradiation of graphene oxide produce reduced graphene oxide. Detailed physical analyses permit to evince the chemical changes of graphene due to the temperature of the film preparation.